ANALYSIS OF PHONEME CHANGES IN THE PACKAGING OF FOOD AND BEVERAGE PRODUCTS IN MINIMARKET SUNGAI SARIK, PADANG PARIAMAN DISTRICT: PHONOLOGY STUDY - Permata, Okma -; Jusmaya, Ance (Politeknik Negeri Bengkalis, 2023)
This research was conducted to see the picture that occurs in phoneme changes in food and beverage product packaging in terms of phonological order, using qualitative descriptive methods. The processing and collection of data is carried out through observation, interviews, and notes. The subjects in this research are products in food and beverage packaging. The location of this research is Mini Market Sarik River, Padang Pariaman Regency. The results of the research show that there are problems regarding adding phonemes, changing phonemes, and refining phonemes that occur in food and beverage product packaging names. Problems like this must be corrected so that they do not become a habit in writing phonemes. Writing phonemes must follow linguistic rules even though the producer's goal is to attract consumers. This problem is not only seen in terms of writing but also seen in terms of speech sounds, namely in the phonological order. Writing that is by linguistic rules can become knowledge for readers or consumers and can be developed in everyday life. Keywords: Indonesian Language, Phonemes, and Phonological Studies